Ideology and the rationality of domination : Nazi germanization policies in Poland - Wolf, Gerhard 1972- (Indiana University Press, 2020)
1. The German quest for Polish land -- 2. War: projecting the "Lebensraum" dystopia onto Poland -- 3. Consolidating power: reinforcing the German occupation regime through population policy -- 4. "Lebensraum": polulation policy in the tug of war between racial hubris and the rational demands of power -- 5. Labor deployment: population policy as a tool of exploitation and assimilation.